2010
DOI: 10.1038/npp.2010.46
|View full text |Cite
|
Sign up to set email alerts
|

Disconnection of the Entorhinal Cortex and Dorsomedial Striatum Impairs the Sensitivity to Instrumental Contingency Degradation

Abstract: The capacity to detect changes in the causal efficacy of actions is mediated by a number of brain areas, including the entorhinal cortex (EC) and the posterior part of the dorsomedial striatum (pDMS). In this study we examined whether interactions between the EC and pDMS are required to detect changes in the instrumental contingency. Rats that received EC-pDMS disconnection lesions, that is, unilateral cell body lesions of the EC and contralateral dopamine depletions of the pDMS, were trained to press two leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 48 publications
4
19
0
Order By: Relevance
“…Selective depletion experiments in the DMS revealed that DA release in this striatal region is important for responding to contextual changes in goal-directed behavioral strategies 40 . This is consistent with the strong input to DMS from the entorhinal cortex 41 , which reads out a hippocampal spatial novelty signal 42 .…”
Section: Discussionsupporting
confidence: 82%
“…Selective depletion experiments in the DMS revealed that DA release in this striatal region is important for responding to contextual changes in goal-directed behavioral strategies 40 . This is consistent with the strong input to DMS from the entorhinal cortex 41 , which reads out a hippocampal spatial novelty signal 42 .…”
Section: Discussionsupporting
confidence: 82%
“…, 2005). In addition, our observation that rats subjected to 6‐OHDA infusions had a near complete and circumscribed striatal DA depletion is consistent with our previous studies using the intra‐pDMS infusions of the same dose/volume of 6‐OHDA (Calaminus & Hauber, 2009; Lex & Hauber, 2010a,b). Likewise, an intra‐striatal infusion of a lower dose of 6‐OHDA than used here profoundly reduced tissue concentrations of DA (> 85%; e.g.…”
Section: Discussionsupporting
confidence: 91%
“…For example, at least two separate groups have reported instances in which animals were differentially sensitive to outcome devaluation and contingency degradation (Corbit, et al, 2002; Lex & Hauber, 2010a; Lex & Hauber, 2010b). In these instances, animals remained sensitive to outcome devaluation, and appeared goal-directed in this measure, but were insensitive to the degradation of the action-outcome relationship.…”
Section: Introductionmentioning
confidence: 99%